KALA LAMPAU TERDEKAT DALAM BAHASA MEE - Niko Kobepa (Universitas Negeri Surabaya, 2015)
Mee (also known as Kapauku, Ekari or Ekagi) is a non-Austronesian language of Wissel Lakeslanguages family of Trans New Guinea Phylum spoken in the Central Highlands of Western New Guinea or West Papua. Mee is also used to refer to its speakers. Mee has an intricate system of Tense, Aspect, Modality and other related categories as will be seen in the paper. This paper aims to discuss one of four past tenses in Mee, namely Immediate Past Tense. Two morphemes that are used- one marking definite and the other indefinite- in this tense will be referred to as necessary. The paper specifically deals with four uses of the tense.